PENATAAN KELEMBAGAAN BADAN PERMUSYAWARATAN DESA BERDASARKAN UU NOMOR 6 TAHUN 2014 - Maulidiah, Sri (UIR PRESS, 2016)
Historically, the existence of villages in Indonesia have existed long before the Unitary Republic of Indonesia (NKRI) exist or are formed. As evidence of the existence of the village, can be seen from the explanation of Article 18 of the Constitution of the Republic of Indonesia Year 1945, where there are approximately 250